Factors Contributing to Domestic Violence Among HIV-Discordant Couples in Kicukiro District, Rwanda - Neema, Uwineza; Monica, Mochama; Okova, Rosemary; Jean, de Dieu Harerimana (Journal of Public Health International, 2025)
Background Domestic violence among HIV discordant couples poses significant public health challenges, affecting treatment adherence and HIV transmission risks. This study examined factors contributing to domestic violence among HIV discordant couples in Kicukiro District, Rwanda. Methods A cross-sectional study was conducted among 384 HIV discordant couples from eleven health centers using stratified systematic sampling. Data were collected through structured face-to-face interviews and analyzed using descriptive statistics and bivariate analysis. Results Domestic violence prevalence was 41.1% physical violence, 34.2% sexual coercion, and 52.3% emotional abuse. Key socio-demographic risk factors included female gender (56% vs. 29% males, p<0.001), older age (61% in ≥55 years vs. 32% in 18-24 years, p=0.004), unemployment (55% vs. 34% formal employment, p=0.014), and financial hardship (63% vs. 25% comfortable situations, p=0.002). Behavioral factors included alcohol use (58% vs. 38%, p=0.021), substance abuse (62% vs. 35%, p<0.001), and poor conflict resolution (72% vs. 25%, p<0.001). Contextual factors like hostile HIV disclosure reactions (68% vs. 34%, p<0.001) and HIV-related stigma (60% vs. 35%, p<0.001) significantly increased violence risk. Conclusions Domestic violence among HIV discordant couples is multifactorial, driven by socio-economic, behavioral, and HIV-related factors. Integrated interventions addressing economic empowerment, conflict resolution skills, stigma reduction, and couple-centered counseling are urgently needed.
Keywords: HIV discordant couples; domestic violence; gender-based violence